The plurality of meaning between Quranic readings and systems theory (Journal of the College of Basic Education, 2022)
It is not possible to look at the multiple meanings of a single text and the differences resulting from the differentQuranic novels and readings; As the foundations of aesthetic creation of the text read? It cannot be said thatCan you give us multiple and different meanings for the same text? If the daily and report text has been putIn order to convey a single meaning to the listener, it is preferable to use a creative text - in addition to being a text Rabbinically - to communicate several meanings of the text.The multiplicity of meanings or their differences is not something that can be disapproved of, as the multiplicity is present in the texts.Literary in general, as a result of the different narrations about a single verse or about a single word.